Răspuns :
Uite câteva:
a)x²-5x+6=0
{a=1
{b=-5
{c=6
∆=b²-4ac=(-5)²-4•1•6=25-24=1
x1,2= - b +/- ✓∆ /2a
[tex]x1 = \frac{ - b + \sqrt{delta} }{2a} = \frac{ - ( - 5) + 1}{2 \times 1} \\ x1 = \frac{5 + 1}{2} = \frac{6}{2} = 3 \\ \\ x2 = \frac{ - b - \sqrt{delta} }{2a} = \frac{ - ( - 5) - 1}{2 \times 1} \\ x2 = \frac{5 - 1}{2} = \frac{4}{2} = 2[/tex]
u)
[tex] - x {}^{2} + x + 6 = 0[/tex]
{a=-1
{b=1
{c=6
∆=b²-4ac=1²-4•(-1)•6=1+24=25
x1,2= - b +/- ✓∆ /2a
[tex]x1 = \frac{ - b + \sqrt{delta} }{2a} = \frac{ - 1 + \sqrt{25} }{2 \times ( - 1)} = \frac{ - 1 + 5}{ - 2} \\ x1 = \frac{4}{ - 2} = - 2 \\ \\ x2 = \frac{ - b - \sqrt{delta} }{2a} = \frac{ - 1 - 5}{ - 2} = \frac{ - 6}{ - 2} = 3[/tex]
t) -3x²-x+2=0
{a=-3
{b=-1
{c=2
∆=b²-4ac=(-1)²-4•(-3)•2=1+12•2=1+24=25
x1,2= - b +/- ✓∆ /2a
✓∆=✓25=5
[tex]x1 = \frac{1 + 5}{ 2 \times ( - 3)} = \frac{ 6}{ - 6} = - 1 \\ x2 = \frac{1 - 5}{ 2 \times ( - 3)} = \frac{ - 4}{ - 6} = \frac{4}{6} {}^{(2} = \frac{2}{3} [/tex]
toate se rezolva la fel